IoT for Residential Monitoring Using ESP8266 and ESP-NOW Protocol - Mochamad Fajar Wicaksono; Myrna Dwi Rahmatya (Universitas Ahmad Dahlan, 2022)
This research aims to create a cluster housing monitoring system. This system combines IoT with the ESP-NOW protocol. In this system, the head of security and homeowners can unify the state of the house through a web application and an android application. The system will send notifications via the web and the LINE messaging application if there is an intrusion or gas leak or no fire is detected. The contribution of this research is to shorten the path and time of data transmission and make it easier for homeowners and heads of security to monitor and take action as soon as possible when something goes wrong in the residential area. The method used in this research is experimental. There are 4 main parts to this system, namely ESP-NOW sender, ESP-NOW receiver, gateway module, and server. All microcontrollers in this system use the NodeMCU ESP8266 because the NodeMCU, apart from being a controller, also functions as a WiFi module. By using the ESP-NOW protocol, it is possible for every microcontroller, both the sender and the receiver, to communicate without using WiFi WAP. In this study, the ESP-NOW sender collected 10 installed in each house to unify the conditions of the house. The ESP-NOW receiver worked to receive data from all senders. Any data received by the receiver will be sent to the gateway serially. The gateway module functions to send all messages to the server online. Application on the server-side built using PHP and MySQL. The display of the system can be opened through the android application or web application. The results of this test indicate that the system is running well with a 100% success proportion where every message from the sender is stored on the server-side, and the application can provide notifications according to the scenario of the system.